PENDAPATAN DAN KETAHANAN PANGAN RUMAH TANGGA PETANI LAHAN SAWAH TADAH HUJANPOLA TANAM PADI DAN JAGUNG DI KECAMATAN KALIANDA KABUPATEN LAMPUNG SELATAN - Fransiska Elisa Adelina; Yaktiworo Indriani; Rabiatul Adawiyah (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2019)
This study aimed to analyze the amount of rainfed farming income, food security, and food consumption pattern of rainfed farmer households (HH).  This research was conducted by survey method at the villages of Taman Agung and Gunung Terang purposely, in which samples constituted of 61 rainfed farmers who were drawn by simple random sampling.  The data of this research was collected in April – May 2018 and analyzed by descriptive qualitativeand quantitative analysis.  The results showed that the rainfed farmer HH achieved the average of rice farming income of Rp15,233,220.63 at the first season and corn farming income of Rp9,097,835.38at the second season.  The HH income was Rp4,080,342.10 per month.  The level of food security as secure was 14.75%, as less was 22.95%, as vulnerable was 29.51%, and as food insecurity was 32.79%.  Consumption pattern obtained 81.97% as good on Variety of the Nutrition Adequacy (VNA) value, 3.28% as sufficient VNA value, 8.19% as moderate VNA value, and 6.56% as poor VNA value. Based on the number of types, the average consumption was 10.43 types of food per day.  The source of food was obtained from the results of farming, planting in the yard, buying, searching, and given.  Nutritional Adequacy Rate of HH for macro nutrients, the most heavily deficit was fat.  For micronutrients, the most deficits was calcium, while those that had normal criteria were vitamin A and iron. Key words: food security, household, income, nutrients